The role of travel patterns in airport duty-free shopping satisfaction: A case study from an Australian regional airport. (September 2019) - Martín, Juan Carlos; Martín-Domingo, Luis; Lohmann, Gui; Spasojevic, Bojana
Abstract: Shopping can be one of the primary motivations for tourism, and commercial revenues are becoming an indispensable source of income for airports. Understanding airport shoppers' satisfaction is thus becoming increasingly relevant for airport operators and remains largely unexplored in the academic literature. This paper contributes to the strand of the literature analysing the satisfaction of duty-free shoppers through a six-item construct that was modelled using a hybrid fuzzy TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method. A questionnaire was administered at the international terminal of a regional airport in Australia. The results show that the differences in terms of place of residence and passengers' destination route are factors influencing the level of shoppers' satisfaction. Residents in Australia and passengers travelling short-haul are more satisfied than non-residents of Australia and those travelling long-haul. With respect to each attribute, the satisfaction elasticities show that shoppers are more elastic in terms of the variety of items available in the shops and the choice of international brands; and satisfaction is less elastic with respect to the ease with which specific items can be found, as well as the 'look and feel' of the shops. Highlights: Duty-free shoppers' satisfaction is analysed with a hybrid-fuzzy TOPSIS method. Place of residence and destination affect airport duty-free shoppers' satisfaction. Australian residents are more satisfied than those who do not reside in Australia. Short-haul passengers are more satisfied than long-haul passengers. Variety of items and international brands impact duty-free shopping satisfaction.